1994
DOI: 10.1021/ac00078a020
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Extraction And Quantification of Fiber Finishes via Online SFE/FT-IR

Abstract: The method of on-line supercritical fluid extraction/Fourier transform infrared spectrometry (SFE/FT-IR) has been applied to the analysis of fiber finishes on fiber/textile matrices. Three different fiber polymer types were examined, each requiring a different finish. Finishes ranged from a single-component poly(dimethylsiloxane) oil to more complex multicomponent finishes that included various surfactants, fatty acid esters and soaps, antioxidants, and oils. The three fiber types tested were polyurethane, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Therefore, one can be sure that the remarkable increase of N concentration on TFT surface originates from the body structure of aramid fiber, suggesting that more surface of naked Twaron fiber appears with the removal of the oily finish by plasma etching and/or chemical reactions. This result can also explain the decrease of O concentration on TFT surface which is mainly from the finish [28]. Compared with the surface C, O, N concentrations of TF sample, the surface chemical composition of TFT are more close to that of the TRT sample.…”
Section: Xps Analysismentioning
confidence: 74%
“…Therefore, one can be sure that the remarkable increase of N concentration on TFT surface originates from the body structure of aramid fiber, suggesting that more surface of naked Twaron fiber appears with the removal of the oily finish by plasma etching and/or chemical reactions. This result can also explain the decrease of O concentration on TFT surface which is mainly from the finish [28]. Compared with the surface C, O, N concentrations of TF sample, the surface chemical composition of TFT are more close to that of the TRT sample.…”
Section: Xps Analysismentioning
confidence: 74%
“…We have reported dye diffusion rates in multiple layers of nylon fabrics [ 4,5,6 j and porous membranes [ 7, 8 j . We observed that surface concentration of dye in multiple layers increased with dyeing time. The increasing surface concentration was attributable to the resistance to dye transfer across the diffusional boundary layer.…”
Section: Discussionmentioning
confidence: 99%
“…The nylon 6 fabric was a taffeta with a fabric density of 42 / cm (70 denier, 12 filaments) for warp yam and 32 / cm (70 denier, 24 filaments) [5] for the weft yam. The diaœtate fabric was a taftèta with a fabric density of 42 / cm (70 denia, 21 filaments) for the wup yam and 30 / cm ( 100 denier, 25 niaments) for the weft…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations